Aromatase inhibitor-associated bone loss and its management with bisphosphonates in patients with breast cancer - Bauer M (Dove Medical Press, 2012)
M Bauer,1 J Bryce,2 P Hadji11University of Marburg, Marburg, Germany; 2National Cancer Institute, Naples, ItalyAbstract: Postmenopausal women have an increased risk of osteopenia and osteoporosis due to loss of the bone-protective effects of estrogen. Disease-related processes may also contribute to the risk of bone loss in postmenopausal women with breast cancer. One of the most common and severe safety issues associated with cancer therapy for patients with breast cancer is bone loss and the associated increase in risk of fractures. This paper reviews the recent literature pertaining to aromatase inhibitor (AI)-associated bone loss, and discusses suggested management and preventative approaches that may help patients remain on therapy to derive maximum clinical benefit. A case study is presented to illustrate the discussion. We observed that AIs are in widespread use for women with hormone receptor-positive breast cancer and are now recommended as adjuvant therapy, either as primary therapy or sequential to tamoxifen, for postmenopausal women. AIs target the estrogen biosynthetic pathway and deprive tumor cells of the growth-promoting effects of estrogen, and AI therapies provide benefits to patients in terms of improved disease-free survival. However, there is a concern regarding the increased risk of bone loss with prolonged AI therapy, which can be managed in many cases with the use of bisphosphonates and other interventions (eg, calcium, vitamin D supplementation, exercise).Keywords: aromatase inhibitors, bisphosphonates, bone loss, breast cancer, estrogen